Additive electronics manufacturing of embedded RF die packaging and multi-chip phased array module - Obeidat, Abdullah S.; Umar, Ashraf; Al-Haidari, Riadh; Alshaibani, W.T.; Dou, Zhi; Alshatnawi, Firas; Gonya, Stephen; Poliks, Mark D.; Hoel, Cathleen; Boyd, Linda; Bellows, Charles; Soto-Valle, Genaro; et al. (Journal of manufacturing processes, 2025)
The demand for high performance electronics is growing in advanced radio frequency (RF) systems. Additive manufacturing has become essential for developing high-density embedded electronics, enabling the integration of small components into a complex RF module and solving the space and interconnect constraints. This work focuses on developing and demonstrating additive manufacturing capabilities and processes that can be used to fabricate high-frequency RF multi-chip module (MCM) with embedded dies and low loss interconnects for weight, cost and size improvement. Firstly, alumina matrix was 3D printed to produce vias and a matrix of pockets for RF chips embedding. The aerosol jet-printed silver interconnects printability, stability and continuity on irregular surfaces were assessed and passed the thermal tests without losing its conductivity. The low noise amplifier (LNA) unit cell was fabricated, including vias filling, dielectric and coplanar waveguide line printing, obtaining RF gain of 10 dB and matching the simulation data. No physical or RF performance changes were observed on the LNA cells after aging at 70 °C/80 % relative humidity for 192 h, demonstrating excellent reproducibility of the additive manufacturing process. The MCM demonstrator including antenna board, 4 × 4 array of embedded LNA dies in alumina plate and control board was successfully assembled using low-temperature 52In48Sn solders. Over-the-air (OTA) test of the demonstrator showed RF gain of 18 dB at 29–30 GHz compared to the case with the amplifier powered off, and it closely aligned with simulation results. This study demonstrates the capability of AM in advancing complex RF module packaging as an alternative to conventional methods. •Developed additive process using 3D printed alumina and printed electronics for complex RF multi-chip module.•Alumina plates with 150 μm deep pockets and 150 μm diameter vias were 3D printed.•Embedded LNAs with printed interconnects in ceramic matrices, obtaining 10 dB RF gain with no changes after reliability tests.•Multi-chip RF module performance shows 18db gain at 29-30 GHz which is aligned with simulation results.